(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The physico-chemical parameters viz., pH, E.C., D.O., B.O.D., C.O.D., total hardness, total alkalinity, chlorides, nitrates and phosphates were analyzed. It has been observed that some of the parameters substantially exceeded the limits when compared with the standards set by BIS and CPCB. The River water was therefore heavily polluted with number of organic and inorganic pollutants. A mechanism for the continuous monitoring of the river water and efforts to control discharge of waste in the River are required.